circFN1 Mediates Sorafenib Resistance of Hepatocellular Carcinoma Cells by Sponging miR-1205 and Regulating E2F1 Expression - Cheng Yang; Zhitao Dong; Han Hong; Binghua Dai; Feihong Song; Li Geng; Jiongjiong Lu; Jiamei Yang; Minhui Xu; Chengjun Sui (Elsevier, 2020)
In recent years, circular RNAs (circRNAs) have been shown to have critical regulatory roles in the resistance to anti-cancer drugs. However, the contributions of circRNAs to sorafenib resistance in hepatocellular carcinoma (HCC) remain largely unknown. The present study aims to explore the involvement of circFN1 in sorafenib resistance and how circFN1 is associated with the miR-1205/E2F1 pathway, which have been demonstrated to mediate this resistance in HCC cells. We investigated the expression of circRNAs in five paired sorafenib-sensitive HepG2 cells and sorafenib-resistant (SR)-HepG2 cells by microarray analysis. The quantitative real-time PCR analysis was used to investigate the expression pattern of circFN1 in HCC patient tissues and cell lines. Then, the effects of circFN1 on sorafenib resistance, cell proliferation, and apoptosis were assessed in HCC in vitro and in vivo. In this study, circFN1 was observed to be upregulated in HCC patient tissues and cell lines. Overexpression of circFN1 in HCC was significantly correlated with aggressive characteristics and served as an independent risk factor for overall survival in patients with HCC. Our in vivo and in vitro data indicated that inhibition of circFN1 enhances the sorafenib sensitivity of HCC cells. Mechanistically, we found that circFN1 could promote the expression of E2F1 by sponging miR-1205. In summary, our study demonstrated that circFN1 contributes to sorafenib resistance by regulating the miR-1205/E2F1 signaling pathway. These results indicate that circFN1 may represent a potentially valuable target for overcoming sorafenib resistance for HCC.